Smart Universal Remote Using Mobile for Home Automation - Chong, Chin Mun (2021)
This project is a Smart Universal Remote design project for academic purposes. It will provide students with the methodology, concept, and design of hardware implementation. In this project, Raspberry Pi 3 Model B+ is a small CPU as a central part of the project with Linux Infrared Remote Control (LIRC). LIRC is an open-source library that allows users to receive and send IR signals with a Linux-based computer system, Raspberry Pi used in this project. IR receiver and IR LEDs must be implemented in the hardware circuit to receive an IR signal sent by IR remote control. Those remote control can be found around the home quickly such as light, fan, TV, home theatre speaker system, and more home devices. After recorded the IR signals as the configure files. Python GUI will use to control the home devices that they have recorded earlier. Then, Ubidots, an IoT platform, is used to make the user control the home device. Using MQTT within Ubidots so that the device can publish the data to the connected and subscribed topic. Then, Telegram Bot used as an additional option to control the IR home devices with a smartphone.